2019
DOI: 10.1158/1541-7786.mcr-18-0777
|View full text |Cite
|
Sign up to set email alerts
|

PTPN11 Plays Oncogenic Roles and Is a Therapeutic Target for BRAF Wild-Type Melanomas

Abstract: Melanoma is one of the most highly mutated cancer types. To identify functional drivers of melanoma, we searched for cross-species conserved mutations utilizing a mouse melanoma model driven by loss of PTEN and CDKN2A, and identified mutations in Kras, Erbb3, and Ptpn11. PTPN11 encodes the SHP2 protein tyrosine phosphatase that activates the RAS/RAF/MAPK pathway. Although PTPN11 is an oncogene in leukemia, lung, and breast cancers, its roles in melanoma are not clear. In this study, we found that PTPN11 is fre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…Tissue‐based microarray expression analysis completed by Demirci Hakan et al have revealed that PTPN18 was differentially expressed in metastatic uveal melanoma in normal whole human blood and tissues prone to metastatic involvement by uveal melanoma. In another research about melanomas reported by Minjung Kim et al, PTPN11 was confirmed to play an oncogenic driver and a novel and actionable therapeutic target for BRAF wild‐type melanoma. Beicheng Sun et al suggested that PTPN12, PTPRN and PTPN18 were associated with the prognosis of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Tissue‐based microarray expression analysis completed by Demirci Hakan et al have revealed that PTPN18 was differentially expressed in metastatic uveal melanoma in normal whole human blood and tissues prone to metastatic involvement by uveal melanoma. In another research about melanomas reported by Minjung Kim et al, PTPN11 was confirmed to play an oncogenic driver and a novel and actionable therapeutic target for BRAF wild‐type melanoma. Beicheng Sun et al suggested that PTPN12, PTPRN and PTPN18 were associated with the prognosis of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 91%
“…PTPN18 belongs to the PTPs that function as tumour suppressors or oncogenes in cancers . Tissue‐based microarray expression analysis completed by Demirci Hakan et al have revealed that PTPN18 was differentially expressed in metastatic uveal melanoma in normal whole human blood and tissues prone to metastatic involvement by uveal melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SHP099 was obtained from MedChem Express, USA (HY‐100388). SHP099 was dissolved in sterile saline and administered by oral gavage at 100 mg/kg daily . SHP099 concurrently binds to the interface of the N‐terminal SH2, C‐terminal SH2 and protein tyrosine phosphatase domains, thus inhibiting SHP‐2 activity through an allosteric mechanism .…”
Section: Methodsmentioning
confidence: 99%
“…For instance, many of the robust dependencies associated with the oncogene BRAF could be interpreted in terms of BRAF's role in the MAPK pathway. BRAF mutation was associated with increased sensitivity to inhibition of its downstream effectors MEK (MAP2K1) and ERK (MAPK1), and increased resistance to inhibition of the alternative RAF isoform gene CRAF (RAF1) and the MAPK regulator PTPN11 ( Figure 3A, 3B) 25 . BRAF mutation was also associated with increased sensitivity to inhibition of PEA15, presumably a result of the requirement of PEA15 for ERK dimerisation and signalling activity 26,27 .…”
Section: Many Robust Genetic Interactions Reflect Known Pathway Strucmentioning
confidence: 99%